Study on highly hydrophilic cellulose hollow fiber membrane contactors for thiol sulfur removal - Yang, Xing (2013)
Dispersion-free reactive extraction of thiol compounds from high-sulfur-contained naphtha products into alkali solutions has been studied in a cellulose microporous hollow fiber membrane contactor. A steady extraction was achieved under a long-term operation of 1 month. The constant partition coefficient of thiol in an infinite dilution between the alkali solution and the oil phase was over 940. In addition, the effects of the tube and shell side hydrodynamics on the mass transfer were investigated. The results indicated that the mass transfer resistance in the oil phase boundary layer contributed to more than 95% of the overall mass transfer resistance, while the membrane resistance only accounted for 2% under the operating conditions. The mass transfer flux of thiol extracted from the real naphtha stream containing 883.4 .gg−1 of sulfur came to 2.40 × 10−5 kg m−2 s−1 , and the mass transfer coefficient reached 3.91 × 10−5 ms−1 . The removal efficiency was up to 99% with octane loss less than 3 mg L−1 when the liquid–liquid volume ratio was 1:1. Furthermore, it was also found that the oil phase flowing at the shell was favorable in fast extraction. A diagram predicting the performance of the contactor for the extraction of sulfur from real naphtha streams was established and the prediction showed a good agreement with the experimental data.